Vivência e instrução escolar: apropriação de conceitos matemáticos na EJA - Denise Alves de Araujo (2017)
The aim of this work is to understand how young adult and adult students from two different classrooms appropriate concepts of school mathematics. The main theoretical and methodological references are: Cultural-Historical Psychology, founded by Lev S. Vigotski and his collaborators, as well as studies derived from that theory; and Ethnography in Education, based on the work of the Santa Barbara Classroom Discourse Group. From the recognition of the social nature of the constitution of humans, Cultural-Historical Psychology enabled us to perceive the processes of appropriation of the mathematical concepts through the interactions established among the people in the classrooms. These processes were evidenced from an ethnography of the classroom which, with its intrinsic relation with the theories of culture, allows to establish a "logic of investigation" that meets the main assumptions of the Cultural-Historical theory. The empirical material was produced in 2015 by means of participant observation in the mathematics classes of two groups of beginners in the Youth and Adult Education Project - 2nd segment. The analyzes revealed the relation between school instruction and adult development, showing how instruction is shaped by the cultural constitution of people, by their experiences, which include their earlier contact with school mathematics, and condition their expectations regarding their return to school; and also by the historical constitution of each event in each one of the two classrooms. For that reason, the same teacher and very similar activities do not produce the same possibilities of participation and learning in both classrooms, demonstrating that the constitution of the psychological functions of human beings is a mediated process.